Crashworthiness response of filament wound kenaf/glass fibre-reinforced epoxy composite tubes with influence of stacking sequence under intermediate-velocity impact load - Supian, A. B. M.; Sapuan, S. M.; Jawaid, M.; Zuhri, M. Y. M.; Ilyas, R. A.; Syamsir, A. (Springer, 2022)
The composite material in energy absorption tube application have gained a tremendous function as sacrificial structure device in automotive, marine, and aerospace engineering. Due to capabilities of composite material in reinforcement structure, many researchers have explored to tailor the composite material properties to withstand into impact load condition. This present study of filament wound kenaf/glass hybrid composite tube was fabricated with three different configurations of hybrid kenaf/glass fibre placement to obtained high capabilities of crashworthiness properties under intermediate-velocity impact load condition. Therefore, this present study has identified the hybridization technique of kenaf/glass fibre which tailored with various intraply stacking sequences parameter of filament winding technique to achieve better impact crashworthiness characteristic when compared with single synthetic glass composite fibre material. The arrangement of hybrid fibres in stacking sequence parameter has found that the hybrid specimen with high kenaf fibre fraction mass have enhanced 68 % of energy absorbing value and the failure mode behaviour was more stable compare to synthetic glass composite tube specimen.